2020
DOI: 10.1002/anie.202008198
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Activity and Stability Origin of BiVO4 Photoanodes with FeNi Oxyhydroxides for Oxygen Evolution

Abstract: Understanding the origin of formation and active sites of oxygen evolution reaction (OER) cocatalysts is highly required for solar photoelectrochemical (PEC) devices that generate hydrogen efficiently from water. Herein, we employed a simple pH‐modulated method for in situ growth of FeNi oxyhydroxide ultrathin layers on BiVO4 photoanodes, resulting in one of the highest currently known PEC activities of 5.8 mA cm−2 (1.23 VRHE, AM 1.5 G) accompanied with an excellent stability. More importantly, both comparativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
138
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(145 citation statements)
references
References 39 publications
6
138
0
1
Order By: Relevance
“…[255] Through density functional theory calculations and experimental studies, it showed that the doping of Fe atoms into the lattice of CoO x produced abundant oxygen vacancies, which significantly improved the interfacial hole injection property of BiVO 4 and reduced the OER onset potential (Figure 19d). Recently, many other advanced co-catalysts have been demonstrated with outstanding performance and stability, such as natural polyphenols/Fe ion, [256] Cu porphyrin, [257] Fe-based (Ni 1−x Fe x and Co 1−x Fe x ) layered double hydroxide, [258][259][260][261] InPO x , [86] molecular Co Cubane, [262] MnO 2 , [263][264][265] and Co 8 -polyoxometalates. [266] In Table 4, it can be seen that by modifying pristine semiconductors with co-catalyst, boosted PEC performance can be achieved due to the significantly enhanced interfacial hole-injection efficiency.…”
Section: Co-catalyst Developmentmentioning
confidence: 99%
“…[255] Through density functional theory calculations and experimental studies, it showed that the doping of Fe atoms into the lattice of CoO x produced abundant oxygen vacancies, which significantly improved the interfacial hole injection property of BiVO 4 and reduced the OER onset potential (Figure 19d). Recently, many other advanced co-catalysts have been demonstrated with outstanding performance and stability, such as natural polyphenols/Fe ion, [256] Cu porphyrin, [257] Fe-based (Ni 1−x Fe x and Co 1−x Fe x ) layered double hydroxide, [258][259][260][261] InPO x , [86] molecular Co Cubane, [262] MnO 2 , [263][264][265] and Co 8 -polyoxometalates. [266] In Table 4, it can be seen that by modifying pristine semiconductors with co-catalyst, boosted PEC performance can be achieved due to the significantly enhanced interfacial hole-injection efficiency.…”
Section: Co-catalyst Developmentmentioning
confidence: 99%
“…As can be seen in Figure S4, Supporting Information, BV film belongs to monoclinic structure (PDF#14-0688), [23] which is in accordance with previous reports. [18,22] The Raman peaks of BV are located at 210.0, 324.0, 366.0, 640.0, 710.0 and 826.0 cm −1 (Figure S5, Supporting Information), meaning that the BV films have been successfully synthesized. [24] Subsequently, the ultrathin amorphous Co(OH) 2 (Figure S6, Supporting Information) nanosheets were uniformly electrodeposited on BV photoanodes (named as BV/Co(OH) 2 ).…”
Section: Synthesis and Characterization Of The Bv/co(oh) X -Ag Photoanodesmentioning
confidence: 99%
“…From Figure S10b,c, Supporting Information, the Bi 4f and V 2P peaks are consistent with values reported previously. [18,22] The high-resolution Co 2p of BV/Co(OH) x -Ag can yield two spin-orbit doublets. The two peaks at 781.8 and 797.7 eV are generated by Co 2+ and another two peaks at 780.2 and 795.3 eV are ascribed to Co 3+ (Figure S11a, Supporting Information).…”
Section: Microscopy (Tem) From Figuresmentioning
confidence: 99%
“…[ 6,7 ] Cost‐competitive metal oxide semiconductors such as Cu 2 O, BiVO 4 , and Fe 2 O 3 are intriguing selections due to their high abundance and easy processability. [ 8–12 ] Nevertheless, oxide‐based photoelectrodes still exhibit low photocatalytic efficiency and poor stability in aqueous electrolytes, limiting their practical applications. [ 13–15 ]…”
Section: Introductionmentioning
confidence: 99%